Integrating miRNA and mRNA Profiling to Assess the Potential miRNA–mRNA Modules Linked With Testicular Immune Homeostasis in Sheep - Li, Taotao; Wang, Xia; Luo, Ruirui; An, Xuejiao; Zhang, Yong; Zhao, Xingxu; Ma, Youji (Frontiers in Veterinary Science, 2021)
Beyond its well-known role in spermatogenesis and androgen production, mammalian testes are increasingly recognized as an immune-privileged organ for protecting autoantigenic germ cells, especially meiotic and postmeiotic germ cells, from systemic immune responses. Despite its importance, the molecular mechanisms underlying this regulation in mammals, including sheep, are far from known. In this study, we searched for the genes associated with testicular immune privilege and assessed their possible modulating mechanisms by analyzing systematic profiling of mRNAs and miRNAs on testicular tissues derived from prepubertal and postpubertal Tibetan sheep acquired by RNA sequencing. We identified 1,118 differentially expressed (DE) mRNAs associated with immunity (245 increased mRNAs and 873 decreased mRNAs) and 715 DE miRNAs (561 increased miRNAs and 154 decreased miRNAs) in postpubertal testes compared with prepuberty. qPCR validations for 20 DE mRNAs and 16 miRNAs showed that the RNA-seq results are reliable. By using Western blot, the postpubertal testes exhibited decreased protein abundance of CD19 and TGFBR2 (two proteins encoded by DE mRNAs) when compared with prepuberty, consistent with mRNA levels. The subsequent immunofluorescent staining showed that the positive signals for the CD19 protein were observed mainly in Sertoli cells and the basement membrane of pre- and postpubertal testes, as well as the prepubertal testicular vascular endothelium. The TGFBR2 protein was found mostly in interstitial cells and germ cells of pre- and postpubertal testes. Functional enrichment analysis indicated that DE mRNAs were mainly enriched in biological processes or pathways strongly associated with the blood–testis barrier (BTB) function. Many decreased mRNAs with low expression abundance were significantly enriched in pathways related to immune response. Also, multiple key miRNA-target negative correlation regulatory networks were subsequently established. Furthermore, we verified the target associations between either oar-miR-29b or oar-miR-1185-3p and ITGB1 by dual-luciferase reporter assay. Finally, a putative schematic model of the miRNA-mRNA-pathway network mediated by immune homeostasis-related genes was proposed to show their potential regulatory roles in sheep testicular privilege. Taken together, we conclude that many immune-related genes identified in this study are negatively regulated by potential miRNAs to participate in the homeostatic regulation of testicular immune privilege of sheep by sustaining BTB function and inhibiting immune responses under normal physiological conditions. This work offers the first global view of the expression profiles of miRNAs/mRNAs involved in sheep testicular immune privilege and how the genes potentially contribute to immune-homeostatic maintenance.